Herophilus of Chalcedon (ca. 330-250 BC) and ocular anatomy. A review - Laios, Konstantinos; Moschos, Marilita M.; Androutsos, George (Italian Journal of Anatomy and Embryology, 2017)
Herophilus of Chalcedon (ca. 330-250 BC) was considered as one of the most important figures of anatomy during the antiquity. Apart from his other works in anatomy very important are also his observations in ocular anatomy. He discovered first the optic nerve and described four tunics in the eye.